Cardiac remodelling in adolescent athletes – sex differences progress through adolescence. (3rd October 2022) - Forsaa, M; Bjerring, A W; Haugaa, K; Smedsrud, M K; Sarvari, S; Landgraff, H W; Hallen, J; Edvardsen, T
Abstract: Background: Cardiac remodelling beyond reference values is well-known in adult athlete's heart. Male endurance athletes are more prone to develop cardiac chambers and wall thickness above reference values. Cardiac remodelling is also described in adolescent athletes, but considered to be moderate compared to adults. However, few studies evaluate adolescent athlete's heart by paediatric echocardiographic reference values. Current paediatric reference values are sex-unspecific and do not include exercise data. The impact of sex and exercise on remodelling in adolescent athlete's heart remains unclear. Purpose: We aimed to study the development of cardiac remodelling and potential sex differences in adolescent athletes. We hypothesized that male adolescent athletes would display greater degree of remodelling compared to female adolescent athletes. Methods: Male (M) and female (F) adolescent cross-country skiers were recruited in a longitudinal cohort study. They were examined with echocardiography at age 12, 15 and 18. Data on exercise was collected at all examinations. We evaluated echocardiographic parameters by paediatric reference values (Z-score: number of standard deviations above estimated mean in the given body surface area). Echocardiographic measures were considered above upper reference value if Z-score was ≥2. Results: Seventy-six athletes were examined at age 12 (48 M, 28 F), 48 at age 15 (34 M, 14 F) and 34 at age 18 (23 M, 11 F). Although Z-scores were within reference values at age 12 (Table 1), a subset of athletes displayed Z-scores ≥2 for end-diastolic intraventricular septum diameter (IVSd, M 13/48=27%, F 5/28=18%) and left ventricular posterior wall thickness (LVPWd, M 6/48=13%, F 2/28=14%). The male group demonstrated enlarged left ventricular mass (LVM) from age 15 (Figure 1). Males had greater left ventricular end-diastolic volume (LV EDV) from age 12. Additional sex differences were evident from age 15 for IVSd, LVPWd and LVM (Table 1). There was no sex difference in exercise hours. Both groups had normal myocardial function through the study period. Conclusion: Cardiac remodelling beyond reference values was observed in athletes of both sexes from early adolescent age. Sex differences were evident from age 12 with further progression. Pathological values for LVM were more frequent in males. These findings suggest that sex differences in exercise-induced cardiac remodelling is more prominent in adolescents than previously reported. Sex and exercise history should be considered in questions of pathology. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): The South-Eastern Norway Regional Health AuthorityCentre for Children and Youth Sport, Norwegian School of Sport Sciences